2011
DOI: 10.1029/2011gl046768
|View full text |Cite
|
Sign up to set email alerts
|

A conduit dilation model of methane venting from lake sediments

Abstract: Methane is a potent greenhouse gas, but its effects on Earth's climate remain poorly constrained, in part due to uncertainties in global methane fluxes to the atmosphere. An important source of atmospheric methane is the methane generated in organic‐rich sediments underlying surface water bodies, including lakes, wetlands, and the ocean. The fraction of the methane that reaches the atmosphere depends critically on the mode and spatiotemporal characteristics of free‐gas venting from the underlying sediments. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
128
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(137 citation statements)
references
References 34 publications
8
128
1
Order By: Relevance
“…This is in stark contrast to the homogenous, cohesive fine-grained estuarine sediment that fills the nearshore basins in the north temperate pockmark fields. Coarser-grained channel fill could promote fluid migration and diffusion along the channel, rather than vertical migration of fluids that occurs in fine-grained sediment (e.g., Jain and Juanes, 2009;Scandella et al, 2011), resulting in gas spatially coincident with paleochannels and minimal seafloor disturbance (Hill et al, 1992).…”
Section: Pockmarks' Relation To Stratigraphymentioning
confidence: 99%
“…This is in stark contrast to the homogenous, cohesive fine-grained estuarine sediment that fills the nearshore basins in the north temperate pockmark fields. Coarser-grained channel fill could promote fluid migration and diffusion along the channel, rather than vertical migration of fluids that occurs in fine-grained sediment (e.g., Jain and Juanes, 2009;Scandella et al, 2011), resulting in gas spatially coincident with paleochannels and minimal seafloor disturbance (Hill et al, 1992).…”
Section: Pockmarks' Relation To Stratigraphymentioning
confidence: 99%
“…The prevailing paradigm is that microbial methanogenesis occurs primarily in anoxic environments (3,4). A commonly observed paradox is methane accumulation in well-oxygenated waters (2,5), which is often assumed to be the result of physical transport from anoxic sediment and water (6)(7)(8) or in situ production within microanoxic zones (9)(10)(11). Two recent studies challenged this paradigm and suggested that microbes in oligotrophic ocean can metabolize methylated compounds and release methane even aerobically (12,13).…”
mentioning
confidence: 99%
“…The ebullition rate, E CH 4 ,s becomes non-zero when bulk CH 4 concentration exceeds a critical value, defined by the hydrostatic load of the water column and sediments layer above at a given depth, z s , as well as by nitrogen concentration at the sediments top Walter et al, 1996). Retention of bubbles in a sediment's skeleton (Scandella et al, 2011) is neglected so that the CH 4 ebullition flux at the sediment's top of the kth column, F B,1,k , is calculated as…”
Section: Methane In Sedimentsmentioning
confidence: 99%
“…This situation is complicated by high vertical and sometimes horizontal variability of gas concentrations in a given lake (Schilder et al, 2013;Blees et al, 2015). Third, when considering gas dynamics in lakes, new physical processes become crucial such as diffusion through the water surface (Donelan et al, 2002), vertical diffusion in metalimnion and hypolimnion, bubble interactions with sediments skeleton (Scandella et al, 2011), and others. Many of these have not been addressed enough so far in both theoretical and experimental studies.…”
Section: Introductionmentioning
confidence: 99%